Using community-based flood maps to explain flood hazards in Northland, New Zealand - Auliagisni W; Wilkinson S; Elkharboutly M (Elsevier Ltd, 2022)
Floods are among the most common and destructive natural disasters in New Zealand, and climate change is anticipated to make them even more frequent and severe. A clear and comprehensive flood map is critical to communicating flood hazard to communities at risk. Mitigation, adapting, and informed decisions making could be efficiently accomplished with the clear flood maps. However, existing flood maps appear to have been developed for professionals, complex, and not easily available for communities living in flood hazard areas. This study examines how, using flood maps, risk communication between local authorities and the communities can be improved. Observational surveys and in-depth interviews were used to acquire descriptive information and in-depth understanding of risks within the communities in the Northland, New Zealand. Thematic analysis of the findings revealed that the current flood maps are not easy to acquire and hard to comprehend. Without knowledge, communities develop a false sense of security, especially where there is inadequate risk communication and engagement with local authorities. This study highlights the need for a greater understanding of integrating community knowledge and experience with the current risk communication plans. Additionally, this study recommends developing more comprehensive and user-friendly flood maps using community-based information.